Saved by silence: Climate change, food insecurity and Gender – Based Violence (GBV) in Chimanimani - Takaindisa, Joyce; Campbell, Raramai (2025)
Climate change is worsening food insecurity and gender inequality in Chimanimani, increasing the risk of gender-based violence. As climate shocks strain households, women face rising domestic abuse but often remain silent to preserve marriages shaped by patriarchal norms.